Utilising patient and public involvement to increase the acceptability of brief CBT for OCD in young people - Waite, P; Klampe, M-L; Walters, S; Salkovskis, P (Cambridge University Press, 2023)
Obsessive Compulsive Disorder (OCD) is a common and debilitating disorder that frequently begins in childhood and adolescence. Previous work (Bolton et al., 2011) has demonstrated that brief CBT (5 sessions), supplemented by therapeutic workbooks, is as effective as more traditional length (12 session) therapist-delivered treatment for adolescents with OCD. However, as was typical at the time, the treatment was developed with very limited patient and public involvement (PPI) and was delivered in the context of a randomised controlled trial which might affect translation to routine child and adolescent mental health services (CAMHS). To be able to implement such treatment within routine clinical services, it is crucial that it acceptable to young people, their families and the clinicians delivering the treatment. The aim of this project was to improve the acceptability of the brief treatment through PPI and consultation with clinicians and consider issues relating to implementation. This was done through written feedback, interviews and focus groups with five adolescents and two parents, and a focus group and a half-day workshop with 12 clinicians. This led to revisions to the workbooks and materials to improve (a) acceptability by updating the design through changes to wording, language, and images and to ensure that they were consistent with values of equality, diversity, and inclusion, and (b) usability by clarifying, adding, removing content, and organising the materials in new ways. We emphasise the importance of continued PPI throughout the project to maximise the translation of findings into practice.